A double blind placebo controlled comparison of verapamil, atenolol, and their combination in patients with chronic stable angina pectoris. Issue 4 (April 1987) - Findlay, I N; MacLeod, K; Gillen, G; Elliott, A T; Aitchison, T; Dargie, H J
Abstract : The efficacy and effect on cardiac function of verapamil 120 mg three times a day and atenolol 100 mg once a day, singly and in combination, were evaluated in 15 patients with angina pectoris. While they were on the combination treatment four patients withdrew from the study. Episodes of angina pectoris and glyceryl trinitrate consumption were significantly reduced only on the combination. On the combination only four patients developed evidence of ischaemia during exercise compared with seven on verapamil and ten on atenolol. ST segment depression at peak exercise, assessed by 16 point precordial mapping, was reduced by all active treatments from 7.1 on placebo to 2.7, 0.9, and 0.6 mm on atenolol, verapamil, and the combination respectively. Mean left ventricular ejection fraction fell significantly from 60% on placebo to 53% on the combination but was unchanged on verapamil and atenolol. Verapamil was an effective alternative to atenolol; the combination was the most effective treatment but was associated with a significant morbidity.